2008
DOI: 10.1007/s00261-008-9404-8
|View full text |Cite
|
Sign up to set email alerts
|

CT enterography vs. capsule endoscopy

Abstract: Small bowel imaging has been revolutionized by CT enterography and capsule endoscopy. We present an overview of both imaging modalities, discuss advantages and disadvantages of each, and compare findings in Crohn's disease, occult gastrointestinal bleeding, and small bowel tumors. Both methods complement each other often providing information that the other one cannot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…A previous study reported that CT enterography identified bleeding sources in 45% of 22 outpatients with OGIB, including three lesions that were missed by capsule endoscopy [11]. Since CT enterography can evaluate extraintestinal diseases, a recent study mentioned that CT enterography is complementary to capsule endoscopy [12]. Particularly, for cases suspected of intestinal stricture or neoplasm, CT enterography is suggested as a first-line diagnostic investigation [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…A previous study reported that CT enterography identified bleeding sources in 45% of 22 outpatients with OGIB, including three lesions that were missed by capsule endoscopy [11]. Since CT enterography can evaluate extraintestinal diseases, a recent study mentioned that CT enterography is complementary to capsule endoscopy [12]. Particularly, for cases suspected of intestinal stricture or neoplasm, CT enterography is suggested as a first-line diagnostic investigation [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…While VCE has been compared with standard radiological examinations, comparison with more modern imaging techniques has been limited [14][15][16][17][18]. Among these recent imaging techniques, computed tomography (CT) enteroclysis has rapidly emerged as a useful tool for the diagnosis of a wide range of small-bowel diseases, including obscure gastrointestinal bleeding [14,17,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ubiquitous nature of CT, its ease of use and rapid results, as well as its more consistent diagnostic yield compared with CE favor its use as the first-line study in patients with OGIB (18). Particularly, for cases with suspected intestinal stricture or neoplasia, CT is recommended as the first-line diagnostic investigation (9,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, computed tomography (CT) is easy to use, provides rapid results, and can evaluate small bowel strictures and extraluminal disease that can not be detected by CE. Because of these advantages, some consider CT as a complementary test to CE (9).…”
Section: Introductionmentioning
confidence: 99%